PRODUCT LABEL DESIGN AND APPLY QR CODE TECHNOLOGY (QR CODE) TO COMMUNICATE AND INCREASING VALUE OF GOODS FOR PROCESSED PRODUCTS CRISPY SHREDDED PORK CASE STUDY OF PRODUCER MAR TU KAWNEAW SAMSI - Saysrikeaw, Yupapin; Wannakayont , Asada; Dumnil, Suchat; Praisin, Aphichai (Journal of MCU Nakhondhat, 2022)
The Objectives of this research article were to 1) develop product labels and 2) assess the quality of labels and product packaging Tools for conducting research are product labels, product packaging. and product label and packaging quality assessment form research method The researcher took the product label information into consideration together with the concept of proper product label design. Then take the product labels and product packaging for quality assessment from experts. The results were analyzed by using basic statistics such as mean and standard deviation. The results of the research were found that 1) product label design results consisted of 1.1) logo, chose the image of the entrepreneur as a symbol. to create an identity And create outstanding features for the product 1.2) Text is divided into 3 parts, namely the operator and the product. Product definition and general information of the product 1.3) Font style Choose images and letters that are easy to spot. outstanding Use the right size To display necessary information and details about the product 1.4) Create spaces by using white, red and yellow to make product labels. It is outstanding, pleasing to the eye and has a balanced composition. 1.5) Selecting and retouching images by using images of entrepreneurs to create product labels and decorate the image by using color elements to make the image look attractive and 1.6) the application of QR code technology (QR CODE) to help communicate information about the story and production methods 2) the results of the label quality assessment Products and product packaging, processed products, crispy pork food vendor Three colors of glutinous rice tou From the overall assessment by experts, it was found that it was at the highest level with a mean of 4.69 and a standard deviation of 0.51.